Incidence and prevalence of uveitis: results from the Pacific Ocular Inflammation Study - Acharya, Nisha R; Tham, Vivien M; Esterberg, Elizabeth; Borkar, Durga S; Parker, John V; Vinoya, Aleli C; Uchida, Aileen (JAMA ophthalmology, 2013)
Uveitis is responsible for a significant proportion of legal blindness in the United States. Currently, there are few population-based reports characterizing the epidemiology of uveitis. To ascertain the incidence and prevalence of uveitis in a Hawaiian population and compare these estimates with those from prior population-based studies. Retrospective, population-based cohort study conducted from January 1, 2006, to December 31, 2007. Kaiser Permanente Hawaii, a multispecialty managed care organization serving approximately 15% of the general Hawaiian population with locations throughout the Hawaiian islands. All patients enrolled in the Kaiser Permanente Hawaii health plan during the study (N = 217,061). Clinical diagnosis of uveitis, either incident or prevalent, during the study determined by an initial search of the electronic medical record database of Kaiser Permanente Hawaii for uveitis-associated International Classification of Diseases, Ninth Revision diagnosis codes and subsequently confirmed through individual record review by a uveitis specialist. Of 217,061 eligible patients, 872 were identified using International Classification of Diseases, Ninth Revision codes and 224 cases of uveitis were confirmed. The overall uveitis incidence rate was 24.9 cases per 100,000 person-years. The annual prevalence rates for 2006 and 2007 were 57.5 and 58.0 per 100,000 persons, respectively. No difference in incidence rate was found by sex (P = .63), but female patients had a higher prevalence (P = .008). Incidence and prevalence increased with older age (P < .001 for incidence and prevalence). Pacific Islanders had a lower prevalence rate than non-Pacific Islanders (2006: P = .09, 2007: P = .04), while white individuals had a higher prevalence rate than nonwhite individuals (2006: P = .07, 2007: P = .01). The incidence and prevalence of uveitis in this population were much lower than in the Northern California Epidemiology of Uveitis Study, but similar to the Northwest Veterans Affairs Study. The results of this study highlight incidence and prevalence estimates in a new population and provide novel comparisons by race. These differences by race raise questions regarding the effects of genetic and environmental influences on the pathophysiology of uveitis.